Impacto da variação de temperatura de incubação na produção de biogás em ensaios de potencial bioquímico de metano - Marenda, William Carlos (2019)
In Brazil, livestock residues are commonly treated in anaerobic digestion (AD) system without heating and thermal insulation, thus operating at ambient temperatures, outside the ideal AD ranges (37 and 55 ° C), which can cause low efficiency and productivity of biogas in digesters. To analyze this impact, residues and effluents resulting from livestock activities (swine, cattle breeding and poultry) were submitted to Biochemical Methane Potential (BMP) tests in different temperature ranges (25, 37 and 55 ° C). In the analyzed substrates, 80% obtained the highest biogas production value at 25 ° C and the coefficient of variation between the obtained BMP results varied between 6% and 15%.